Changes in zooplankton diversity and distribution pattern under varying precipitation regimes in a southern temperate estuary - Primo, Ana Lígia (2009)
http://www.sciencedirect.com/science/article/B6WDV-4VGF3YJ-5/2/0532a272b92cfc2de9a24d92edc5265b